Anatomy of Musculoskeletal System in the Light of the Qur’an and Hadith - Yusof, Nurul Asyiqin; Che Mohamad, Che Anuar; Hassan, Ahmad Nizam (IIUM Medical Journal Malaysia, 2018)
The integration of human knowledge between the medical and health care sciences with revealed knowledge was established since the era of Al-Razi (Rhazes), Ibn Sina (Avicenna), Ibn Rushd (Averroes), AlZahrawi (Albucasis) and others. However, the glorious period of Islamic medicine gradually declined after the period of ’Abbasiyyah and ’Uthmaniyyah. At present, many scholars tend to separate the modern medicine and the revealed knowledge, resulting in the disconnection between these two fields. There is little to suggest the presence of reference collections that integrate the Qur’an and Hadith with medicine. This review aimed to fill that gap. Relevant Qur’anic verses and authentic Hadith of the Prophet Muhammad (peace be upon him; henceforth PBUH) in relation to a specific field in medicine i.e. the anatomy of human musculoskeletal system was extracted. The musculoskeletal system is unique in which it forms the ‘backbone’ of normal human posture. The system plays a vital role in maintaining human daily activities. From this review, it is noted that many Qur’anic verses and Hadith relate to the musculoskeletal system. A few examples include the number human joints and its relationship with the daily prayers (Salah), the daily charitable act recommended to all Muslim, the coccyx bone that is indestructible and shall be the source for human resurrection during the hereafter, and others. These examples necessitate for a more in-depth analysis to enlighten the revealed knowledge from the medical perspective.